2020
DOI: 10.1101/2020.01.17.911099
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

T cell responses induced by attenuated flavivirus vaccination are specific and show limited cross-reactivity with other flavivirus species

Abstract: T cell responses induced by attenuated flavivirus vaccination are specific and show limited cross-1 reactivity with other flavivirus species. 2 Abstract word count: 247 24 Manuscript word count: 6692 25 Abstract 26Members of the flavivirus genus share a high level of sequence similarity and often circulate in 27 the same geographical regions. However, whether T cells induced by one viral species cross-28 react with other related flaviviruses has not been globally addressed. Here, we tested pools of 29 epitopes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The apparent higher conservation of CD8 + T cell epitopes is to be expected based on the shorter length of HLA class I binding peptides (usually 9-10 amino acids) as compared to their class II counterparts (13-17. This effect is counterbalanced by CD8 + T cells being generally less tolerant of amino substitutions as compared to CD4 + T cells (Grifoni et al, 2020a;Weiskopf et al, 2014). Overall, we observed that the effect of the variant mutations on the global CD4 + and CD8 + T cell responses was negligible.…”
Section: Discussionmentioning
confidence: 68%
“…The apparent higher conservation of CD8 + T cell epitopes is to be expected based on the shorter length of HLA class I binding peptides (usually 9-10 amino acids) as compared to their class II counterparts (13-17. This effect is counterbalanced by CD8 + T cells being generally less tolerant of amino substitutions as compared to CD4 + T cells (Grifoni et al, 2020a;Weiskopf et al, 2014). Overall, we observed that the effect of the variant mutations on the global CD4 + and CD8 + T cell responses was negligible.…”
Section: Discussionmentioning
confidence: 68%